Appearance‐Related Communication Mediates the Link Between Self‐Objectification and Health and Well‐Being Outcomes. (8th July 2014) - Arroyo, Analisa; Segrin, Chris; Harwood, Jake
<x xml:space="preserve">Abstract</x> Grounded in objectification theory, the 2 studies presented here predicted that self‐objectification is positively related to appearance‐related communication (i.e., fat talk and old talk), and, in turn, appearance‐related communication is associated with health and well‐being outcomes. Results from Study 1, which investigated only fat talk, revealed that fat talk significantly mediated the relationship between self‐objectification and body dissatisfaction, drive for thinness, bulimia, and self‐esteem. Study 2 sought to replicate the findings from Study 1, as well as extend appearance‐related communication to old talk. Fat talk was found to mediate the relationships between self‐objectification and body dissatisfaction, drive for thinness, bulimia, depression, and diet. Old talk significantly mediated the relationships between body dissatisfaction, drive for thinness, and bulimia.